Teacher self-efficacy and reasons for choosing initial teacher education programmes in Norway and New Zealand. (April 2023) - Berg, David A.G.; Skaalvik, Einar M.; Asil, Mustafa; Hill, Mary F.; Uthus, Marit; Tangen, Truls N.; Smith, Jeffrey K.
Abstract: In samples of teacher education students in New Zealand and Norway, we explored their reasons for choosing teaching and their sense of self-efficacy for teaching. We examined the factor structure of the newly developed Reasons for Choosing Teacher Education Scale (RCTES) and the established Norwegian Teacher Self-Efficacy Scale (NTSES). The factor structure of the NTSES and the RCTES were consistent with expectations and previous research. We found that altruism, personal fit with teaching, and job security were the strongest reasons for going into teaching in both samples, and that teacher self-efficacy is related to motives for entering initial teacher education. Highlights: Teacher self-efficacy is related to motives for initial teacher education The NTSES found to have potential when used with preservice teachers Introduction of the Reasons for Choosing Teacher Education Scale Norwegian participants more conservative in responses to two instruments than New Zealanders